2013
DOI: 10.15415/mjis.2013.12010
|View full text |Cite
|
Sign up to set email alerts
|

Profit Analysis of Non-Identical Parallel System with Two Types of Failure Using Discrete Distribution

Abstract: This paper has analyzed the two non-identical operative parallel system considering two units (automatic and manual one) by using regenerative point technique. For the automatic unit the concept of inspection policy has been introduced to detect the kind of failures (major or minor) before being repaired by some repair mechanism. But the manual unit is free from such inspection policy. Various important measures of reliability i.e MTSF, steady state availability, busy period of repairman and inspector, profit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…In this paper, they assumed both the distributions for the repair time are poisson but here in this our work we are having correlated failure and repair. Bhatti et al (2011) shown the interest in discussing the analysis regarding profit of two-unit standby framework with more than one kind of failure under different testing policy for non-active or failed units and most importantly they used discrete distribution. Berrade et al (2013) presented a research work which was based on the analysis of reliability under the assumption that inspection of the unit is not perfect, and replacement is required.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, they assumed both the distributions for the repair time are poisson but here in this our work we are having correlated failure and repair. Bhatti et al (2011) shown the interest in discussing the analysis regarding profit of two-unit standby framework with more than one kind of failure under different testing policy for non-active or failed units and most importantly they used discrete distribution. Berrade et al (2013) presented a research work which was based on the analysis of reliability under the assumption that inspection of the unit is not perfect, and replacement is required.…”
Section: Introductionmentioning
confidence: 99%
“…They assumed that repaired unit would work as well as new one after repair. Bhatti et al (2011) discussed two identical unit cold standby systems with single repair man facility where concept of inspection policy has also been introduced for detecting the kind of failures (major or minor) before the failed unit get repaired by repairman. Narang et al (2012) discussed the profit analysis of two unit standby oil delivering system with three types of failure complete failure, where normal to partial failure and partial to complete failure was also analyzed.…”
Section: Introductionmentioning
confidence: 99%